Type 2 Myocardial Infarction on the Background of Coronary Vasospasm and Invasive Tactics of Its Diagnosis and Treatment - D. Yu. Gamayunov; A. N. Kalyagin; N. M. Balabina; A. V. Sinkov; E. S. Chujko; E. R. Kiseleva; K. B. Gajnutdinov; A. V. Sorzheev; E. O. Bykov (SINAPS LLC, 2023)
Currently, type 2 myocardial infarction is a rather significant problem, both in terms of diagnosis and treatment. Myocardial infarction without obstructive coronary artery damage occurs in 5-10 % of patients with a myocardial infarction. Optimal strategies for the diagnosis and treatment of patients with myocardial damage associated with non-thrombotic mechanisms have not yet been determined. The article describes a clinical observation of type 2 myocardial infarction on the background of vasospasm, as well as diagnostic and therapeutic tactics in this clinical situation. The main provisions: the patient was 22 years old in the cardiology department due to the pain syndrome behind the sternum for the first time in his life and an increase in body temperature to 37.5 C. From anamnesis: active bodybuilding, taking testosterone in injectable form. The electrocardiogram revealed changes in the type of transmural myocardial ischemia without the dynamics characteristic of myocardial infarction. Troponin I (quantitative test) - 2.1 ng/ml at laboratory reference values of 0.010-0.023 ng/ml. A diagnostic search was conducted for myocardial infarction and acute pericarditis. For the purpose of differential diagnosis, coronary angiography was performed, during which dynamic stenosis of the posterior descending artery was revealed. The decision to stent the vessel was not made. Echocardiography revealed areas of local contractility disorders. The data of the examination showed in favor of myocardial infarction without coronary artery obstruction (type 2). Taking into account the absence of occlusive-stenotic lesions of the coronary arteries, the presence of vasospasm, 1 platelet aggregation inhibitor, medium-dose statins, isosorbide dinitrate, calcium channel blocker, angiotensin-converting enzyme inhibitor was prescribed.   Conclusion. Invasive tactics made it more likely to diagnose type 2 myocardial infarction and prescribe the most optimal drug therapy.